1992
DOI: 10.1182/blood.v80.3.825.825
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic assessment of quality of life after autologous bone marrow transplantation

Abstract: To determine the quality of life in adult patients after autologous bone marrow transplantation (BMT), we administered a questionnaire to a cohort of patients seen at a single referral-based center. The sample included adults 18 years and older during the 1 year following an autologous BMT. Both disease-free patients and those who relapsed with 1-year of follow-up data available were included. Of 59 eligible patients, 58 (98%) responded to the questionnaire. Patients completed a telephone questionnaire adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 0 publications
1
25
0
7
Order By: Relevance
“…The mean scores on the sexual subscale were in line with other reports employing the CARES (Rusten et al, 1999;te Velde et al, 1996;Gritz et al, 2000). Problems in relation to sexuality, both with respect to interest and activity, have frequently been reported after HDC and stem cell transplantation, with percentages varying from 14 to above 30%, depending on design and methodology (Wingard et al, 1992;Chao et al, 1992;Vose et al, 1992). One prospective report concluded that pre-treatment difficulties in the sexual domains did not change significantly within the first year (Marks et al, 1997), while another demonstrated a higher frequency of problems, increasing over time in women compared with men (Syrjala et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The mean scores on the sexual subscale were in line with other reports employing the CARES (Rusten et al, 1999;te Velde et al, 1996;Gritz et al, 2000). Problems in relation to sexuality, both with respect to interest and activity, have frequently been reported after HDC and stem cell transplantation, with percentages varying from 14 to above 30%, depending on design and methodology (Wingard et al, 1992;Chao et al, 1992;Vose et al, 1992). One prospective report concluded that pre-treatment difficulties in the sexual domains did not change significantly within the first year (Marks et al, 1997), while another demonstrated a higher frequency of problems, increasing over time in women compared with men (Syrjala et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…We have previously published prospective reports on HRQOL assessed by the European Organisation for Research and Treatment of Cancer Core Quality of Life questionnaire (EORTC QLQ-C30) (Hjermstad et al, 1998A, 1999B) and on anxiety and depression assessed by the Hospital Anxiety and Depression Scale (HADS) in this patient population (Hjermstad et al, 1999B). Through literature searches we have identified an additional ten prospective studies which exceeded the immediate transplant period and included at least 40 patients with haematological malignancies (Syrjala et al, 1993;Meyers et al, 1994;Jenkins et al, 1994;Broers et al, 2000Broers et al, , 1998McQuellon et al, 1997;Chao et al, 1992;Baker et al, 1999;Fife et al, 2001;Tschuschke et al, 2001). The results were not consistent regarding the patients' HRQOL after stem cell transplantation, possibly due to differences in study design, outcome measures and time of follow-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(33)(34)(35)(36) BI satisfaction appears to get better with a longer time after transplantation. (37)(38)(39) When BI concerns are present, women tend to have poorer BI than men after receiving heart, kidney, or skin allografts. (34,40) In addition, in women, BI is less likely to improve with transplantation.…”
Section: Original Article | 713mentioning
confidence: 99%
“…Quality-of-life studies show that patients are able to return to their daily lives within 6 to 12 months and achieve a high quality of life. 107 Because inflammatory disease does not fulfil the criteria of clearly increased mortality to justify HSCT, it seems prudent that the patient must be fully informed and ongoing results should be analysed by a safety board. Allo-SCT has a transplant-related mortality rate of 15%-30%.…”
Section: Problems With Transplantationmentioning
confidence: 99%